ANALISA UNJUK KERJA KOMPOR BIOMASSA TERHADAP KARAKTERISTIK BIOPELET ECENG GONDOK (Eichhornia crassipes) DENGAN GETAH DAMAR (Agathis loranthifolia) - Zikri, Ahmad (Politeknik Negeri Sriwijaya, 2019)
Fossil fuels are non-renewable energy source that will lead to reduction in the potential for fossil energy, especially petroleum and natural gas. Various solutions have been offered by scientists in the world for alternative fossil fuels. One new renewable energy alternative that can reduce the fuel consumption of oil obtained from the fossil is to use biomass energy. The purpose of this research is to find the resin sap with different composition and diameter to find the best biopelet made from water hyacinth. In this study, mixing of 5%, 10%, and 15% damar resin , and variation of diameter 6mm and 8mm, respectively. The mixture is printed into biopelet then tested to determine the value of heat, biopelet flame test, density, and proximate analysis. From the results of the study is known that the best composition of biopelet is a sample 15% resin gum with a diameter of 6mm. In this composition yields calorific value of 5400.1524cal/gr, moisture content of 0.9887%, density 0.8368gr/cm3, ash content 7.9204%, volatile matter 62.9322%, fixed carbon 28.1587%, flame initial time 8.02sec and boiling time 1 liter water 8.21 minutes. The calorific value and the proximate analysis have fulfilled the SNI 8021 - 2014 and EMPLEMENT PERMEN NO. 47/2000.